*informatics: Identifying and Tracking Informatics Sub-Discipline Terms in the Literature - Chen, E. S.; Sarkar, I. N. (Methods of Information in Medicine, 2015)
Objective: To identify the breadth of informatics sub-discipline terms used in the literature for enabling subsequent organization and searching by sub-discipline.Methods: Titles in five literature sources were analyzed to extract terms for informatics sub-disciplines: 1) United States (U.S.) Library of Congress Online Catalog, 2) English Wikipedia, 3) U.S. National Library of Medicine (NLM) Catalog, 4) PubMed, and 5) PubMed Central. The extracted terms were combined and standardized with those in four vocabulary sources to create an integrated list: 1) Library of Congress Subject Headings (LCSH), 2) Medical Subject Headings (MeSH), 3) U.S. National Cancer Institute Thesaurus (NCIt), and 4) EMBRACE Data and Methods (EDAM). Searches for terms in titles from each literature source were conducted to obtain frequency counts and start years for characterizing established and potentially emerging sub-disciplines.Results: Analysis of 6,949 titles from literature sources and 67 terms from vocabulary sources resulted in an integrated list of 382 terms for informatics sub-disciplines mapped to 292 preferred terms. In the last five decades, “bioinformatics”, “medical informatics”, “health informatics”, “nursing informatics”, and “biomedical informatics” were associated with the most literature. In the current decade, potentially emerging sub-disciplines include “disability informatics”, “neonatal informatics”, and “nanoinformatics” based on literature from the last five years.Conclusions: As the field of informatics continues to expand and advance, keeping upto-date with historical and current trends will become increasingly challenging. The ability to track the accomplishments and evolution of a particular sub-discipline in the literature could be valuable for supporting informatics research, education, and training.
Keywords: Informatics; publications; controlled vocabulary; bibliometrics